Flexible polyimide-based hybrid opto-electric neural interface with 16 channels of micro-LEDs and electrodes. (December 2018) - Ji, Bowen; Guo, Zhejun; Wang, Minghao; Yang, Bin; Wang, Xiaolin; Li, Wen; Liu, Jingquan
Abstract In this paper, a polyimide-based flexible device that integrates 16 micro-LEDs and 16 IrOx -modified microelectrodes for synchronous photostimulation and neural signal recording is presented. The 4 × 4 micro-LEDs (dimensions of 220 × 270 × 50 μm3, 700 μm pitch) are fixed in the SU-8 fence structure on a polyimide substrate and connected to the leads via a wire-bonding method. The recording electrodes share a similar fabrication process on the polyimide with 16 microelectrode sites (200 μm in diameter and 700 μm in pitch) modified by iridium oxide (IrOx ). These two subparts can be aligned with alignment holes and glued back-to-back by epoxy, which ensures that the light from the LEDs passes through the corresponding holes that are evenly distributed around the recording sites. The long-term electrical and optical stabilities of the device are verified using a soaking test for 3 months, and the thermal property is specifically studied with different duty cycles, voltages, and frequencies. Additionally, the electrochemical results prove the reliability of the IrOx -modified microelectrodes after repeated pressing or friction. To evaluate the tradeoff between flexibility and strength, two microelectrode arrays with thicknesses of 5 and 10 μm are evaluated through simulation and experiment. The proposed device can be a useful mapping optogenetics tool for neuroscience studies in small (rats and mice) and large animal subjects and ultimately in nonhuman primates. Precise multisite control of neural activity with opto-electric device A durable, flexible device can be implanted on rat brains to precisely turn on nerve cells using light and synchronously record their activities. Jingquan Liu and colleagues from Shanghai Jiao Tong University in China combined reliable wire-bonding micro-LED and modified microelectrode arrays to design a device that can more precisely target local brain cortex with light than the currently used optic fibers in optogenetics. In this field of research, scientists genetically alter nerve cells to produce light-sensing proteins, allowing them to control nerve activity with light. This could lead to advancements in the treatment of diseases like Parkinson's and depression. The new device retains good performance after 3 months of soaking test and repeated pressing and friction for 5000 times. It is a useful multifunctional optogenetics tool and potentially integrated with wireless technology.